(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
أجريت تجربة حقلية في محطة بحوث حوط التابعة لمركز البحوث العلمية الزراعية في محافظة السويداء – الهيئة العامة للبحوث العلمية الزراعية خلال الموسم الزراعي 2016-2015 لدراسة أثر مستويات مختلفة من الري الناقص مع مستويات تسميد مختلفة من كومبوست قمامة المدن في بعض الخواص المورفولوجية وإنتاجية نبات الخس, ومقارنتها بالسماد المعدني شائع الاستخدام, صممت التجربة كقطع منشقة بثلاث مستويات للري ينشق عن كل منها أربع معاملات تسميد بالإضافة للشاهد غير المعامل وبثلاثة مكررات لكل منها. درس البحث ارتفاع النبات (H) وعدد أوراقه (N) والمساحة الورقية للورقة الواحدة LAL و للنبات الكامل LAP ومؤشر المساحة الورقية LAI, بالإضافة للوزن الرطب لرأس الخس والإنتاجية الكلية للمساحة المزروعة. وتشير نتائج تفاعل معاملات الري والتسميد إلى الأثر الإيجابي الواضح للإضافات العضوية على المؤشرات الإنتاجية وفعالية تطبيق تقنية الري الناقص, وإلى تفوق المعاملة T11 تفوقاً معنوياً في كل المؤشرات المُقاسة على باقي المعاملات بزيادة في الغلة النهائية بلغت %169 مقارنة بالمعاملة T15 و %428 مقارنة بالمعاملة T35. كما تشير النتائج لإمكانية التوفير بنسبة %25 من كمية مياه الري المستهلكة باستخدام كومبوست قمامة المدن بدلاً عن السماد المعدني, و تبيّن أن الخليط العضوي المعدني حقق غلة أفضل بنسب بلغت (53 – 44 - 29) % مقارنة بالسماد المعدني المفرد في مستويات الري الثلاث المدروسة (T3 – T2- T1) على التوالي. تمنح هذه النتائج المزارع خيارات واسعة ينتقي منها ما يناسب المتاح لديه من مستلزمات الإنتاج, وفكرة واضحة عن الغلة المتوقعة بحسب المعاملة المختارة. A field experiment was carried out in Hout research station- Agriculture research center in Swaida – General Commission For Scientific Research Agricultural during the growing season of 2015-2016 to study the effect of different levels of deficit irrigation with different levels of town refuse compost (TRC)on some morphological parameters and the productivity of lettuce and compare it with the common mineral fertilizers. The experiment was designed as a split block design with three levels of irrigation, each level has four fertilizing treatments and control with three replicates. The research has studied the plant height (H), the number of its leaves (N) ,the leaf area (LAL), the plant’s leaves area (LAP), the leaves area index (LAI), in addition to the lettuce head’s fresh weight and the total productivity of the planted area. The irrigation and fertilizing interaction results indicate to the obvious positive effect of the organic additions on the productivity parameters and the efficiency of deficit irrigation, and the significant superiority of T11 treatment in all of the measured parameters in compare with the other treatments with an increased final yield of %169 comparing with T15 and % 428 comparing with T35. The results also indicate to the possibility of saving %25 of the consumed amount of irrigation water by using TRC instead of mineral fertilizer , and reveal that the organic- mineral combination achieved a better yield with percentages of ( 29- 44 – 53 )% comparing with single mineral fertilizer in the three studied irrigation levels (T1-T2-T3) respectively. These results give the farmer a wide range of possibilities to choose what suits his available productivity needs , and a clear idea about the expected yield according to the chosen treatment.